We Don T Want Any More Promises. Historical Time, Expectations and Social Conflict in the Mobilization of Tenant Families in the First Years of the Transition to Democracy; ["Ya No Queremos Más Promesas". Tiempo Histórico, Expectativas y Conflicto Social en la Movilización de Las Familias Allegadas en Los Primeros Años de la Transición a la Democracia] - Moyano-Barahona, C; Braithwaite-Castillo, S (Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura, 2023)
This article analyzes the social demands of the tenant families in Santiago, Chile between 1990 and 1994, wondering how they participated in the construction of the historical time after the end of the dictatorship. In this sense, we propose that the experience of the transition was configured from non-linear temporalities or adjusted to the hegemonic discourse of the concertationist elite, which tried to install "waiting" as the axis of democratic consolidation in the future, mainly through the containment of the conflict of the present. To do this, we trace back the main collective actions of the settlers in the first four years of civil government and question the uniformity of the transitional experience. © 2023 Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura. All rights reserved.